CRIMINAL ACT OF MISUSE OF ELECTRONIC MONEY WHICH HAMS CUSTOMERS (CASE STUDY OF MEDAN FINANCIAL SERVICES AUTHORITY) - Zikirullah, Affan (Inspiring Law Journal, 2024)
In the last few years, many customers have been harmed by the actions of irresponsible people. People often take advantage of technological developments to take advantage of technology itself as a weapon (cybercrime). This type of crime then developed and became generally known as "skimming", "cracking", "carding", and "malware". The aim of this research is: To find out about criminal acts of misuse of electronic money. To Find Out Criminal Liability for Misuse of Electronic Money. To Know and Analyze Legal Protection for Bank Customers who lose deposit funds at Automated Teller Machines (ATMs). This research was conducted using normative juridical legal research (normative legal research method). The normative juridical research method is library legal research which is carried out by examining library materials or secondary data alone. Based on the research results, it is understood that the regulation of criminal sanctions for criminal acts of account burglary via ATM in the Criminal Code for theft is contained in Articles 362-365, in Law Number. 11 of 2008 concerning Information and Electronic Transactions (ITE). The criminal liability of perpetrators of misuse of electronic money can be explained as follows. First, the criminal liability of perpetrators of misuse of electronic money in Law Number 19 of 2016 concerning Electronic Information and Transactions includes illegal access, forgery, falsification of identity, alteration or destruction of electronic data related to electronic money. In an effort to protect customer funds, the government through the Consumer Protection Law, as well as through the Banking Law, established the Deposit Insurance Corporation (LPS) and required each bank to guarantee public funds deposited in the bank concerned. Through Bank Indonesia Regulations, it has also been regulated to protect customer funds, so these regulations are used to carry out mediation in resolving banking disputes